Effect of three legumes species on the fertility of a subhumid tropic Luvisol - Cobian-Nuñez, Diana Alejandra; Montañez-Escalante, Patricia Irene; Luis,; Estrada-Medina, Héctor; Jiménez Osornio, Juan José (Ecosistemas y Recursos Agropecuarios, 2022)
Conventional agriculture with the establishment of mono- cultures and the indiscriminate use of pesticides negatively impacts soil fertility. Legume cultivation is an alternative to improve soil conditions and produce food. Therefore, the physical and chemical properties of the soil were determined before and after cultivation of Phaseolus vulgaris, Vigna unguiculata and Vigna radiata. Before starting the crop, the producer evaluated the quality of the soil using qualitative visual indicators. Three treatments were established under a randomized complete block design and with analysis of variance the physicochemical properties were compared before and after cultivation. The quality of the soil was moderate both by the visual evaluation and by the chemical analysis carried out. Treatment effects were observed in CIC and Ca values, which decreased after cultures. The polyculture of leguminous species contributes to improving soil conditions.
Keywords: Key words: sustainable agriculture; nutrient; Phaseolus vulgaris; Vigna radiata; Vigna unguiculata..